Conflict law : the influence of new weapons technology, human rights and emerging actors - Boothby, William H. (Den Haag, The Netherlands : T.M.C. Asser Press, 2014)
In this, the second decade of the 21st Century, the law relating to conflict is confronted by a number of challenges this book seeks to identify and to discuss. Topics as diverse as the evolving spectrum of conflict, innovations in weaponry, automated and autonomous attack, the depersonalisation of warfare, detention operations, the influence of modern media and the application of human rights law to the conduct of hostilities are examined to see to what extent existing legal norms are under attack. The book takes each topic in turn, explains relevant provisions of contemporary law and analyses exactly where the legal problem lies. The analysis then develops the theme, examining for example the implications of current rules as to deception operations for certain applications of cyber warfare.
Includes bibliographical references.
Keywords: War and emergency legislation; Weapons -- Technological innovations; International law and human rights